Chronology, stratigraphy and palaeoenvironmental interpretation of a Late Pleistocene to mid‐Holocene cave accumulation on Kangaroo Island, South Australia. (3rd May 2013) - McDowell, Matthew C.; Bestland, Erick A.; Bertuch, Fiona; Ayliffe, Linda K.; Hellstrom, John C.; Jacobsen, Geraldine E.; Prideaux, Gavin J.
<x xml:space="preserve">Abstract</x> Chronological, sedimentological and geochemical analyses of a clastic infill from Kelly Hill Cave (5K1), Kangaroo Island, document a palaeoenvironmental record that spans from the Late Pleistocene to the middle Holocene. We AMS radiocarbon‐dated bone collagen and U–Th‐dated speleothem to determine that fossiliferous sediments were deposited between >20 ka and 7 ka ago. Most of the 15 sedimentary layers are dominated by sand‐ and silt‐sized quartz that is physically and geochemically comparable with surface soils in the Kelly Hill area. Late Pleistocene and Last Glacial Maximum strata are represented primarily by homogeneous, poorly sorted quartz‐rich sediments that contain little organic matter, but include a thin layer composed largely of silt‐sized clay pellets that resemble sediments deflated from playa lakes. Microstructures observed in petrographic slides indicate that, with the exception of one layer, all sediments experienced little reworking once deposited in the cave. Some layers display pedogenic microstructures such as redeposited clays and opaline silica infilling that indicate postdepositional modification; that is, cave‐floor soil development. Overlying Holocene‐aged sediments also consist mainly of quartz but have much greater organic matter content. Some of these sediments have been strongly influenced by re‐precipitated organic matter that appears to have been transported into the cave via vadose drip water. The presence of dissolved organic matter in soil/vadose waters suggests a high vegetation density and acidic soils, which are congruent with the more equitable climatic conditions characteristic of the Holocene. The sediments described here provide a valuable palaeoenvironmental record that will facilitate future interpretation of associated vertebrate fossils.